Efficacy of Evidence Based Practice (EBP) Guideline to Prevent and Treat Breast Engorgement among Post Caesarean Mothers in Selected Hospital in Mangalore - Thomas, Timi; Devi, Elsa Sanatombi; George, Linu Sara (Journal of Health and Allied Sciences NU, 2017)
Introduction: Early initiation of breast feeding has long been recognized as one of the most important contributor to mothers' as well as infants' health. Breast feeding should be initiated within half an hour and two hour of birth in normal vaginal delivery and caesarean section respectively. A recent systematic review regarding the timing of breast feeding initiation shows that if newborns are exposed to breast feeding at the early stage, they are much more likely to adhere to breast feeding and ultimately have better outcome in terms of less incidence of breast engorgement.Objectives: The objectives of the study were to identify the early initiation of breast feeding by post caesarean mothers using observational check list, to train the staff nurses regarding the EBP guideline to prevent and treat breast engorgement among post caesarean mothers, to find the difference between pre test knowledge score and post test knowledge score among staff nurses on prevention and treatment of breast engorgement using structured knowledge questionnaire, to assess the effectiveness of EBP guideline to prevent and treat breast engorgement among post caesarean mothers in terms of reduction in the severity of breast engorgement before and after the implementation of EBP guideline using modified six point engorgement scale.Methods: In this study, one group pre test post test design was chosen. The study was conducted at KMC Hospital Attawar, Mangalore. The population in this study comprised of prime post cesarean mothers and staff nurses who are available at the period of data collection at KMC Hospital, Attawar, Mangalore. The calculated sample size for post caesarean mothers is 50 ad staff nurses are 20. The following tools were used to collect the data from the study samples. 1) Baseline characteristics - post caesarean mothers and staff nurses 2) Structured knowledge questionnaire on prevention and treatment of breast engorgement 3) Observational checklist to identify early initiation of breast feeding 4) Modified six point engorgement scale to assess the severity of breast engorgement. The data were collected and analyzed by using descriptive and inferential statistics by SPSS package version 16.Results: The study results shows, Out of the 50 mothers, 26 (52%) of the mothers had previous information regarding breast engorgement. 14 (53%) of the mothers had received information from family members/ relatives and friends meanwhile 8 (31%) had mass media as a source of information and 4 (16%) had information from their health professionals. Most of the post caesarean mothers were practicing early initiation of breast feeding. Regarding the total practice score for the early initiation of breast feeding it was 6.38 ± 0.696 and it ranged from 5 to 7 with a median 6.Conclusion: The study has revealed that, most of the post caesarean mothers were practicing the early initiation breast feeding practices.
Keywords: EBP Guideline; Breast engorgement; Post caesarean mothers